Characterization of human Gadd45, a p53-regulated protein. - France Carrier; Melvyn Smith; I Bae; Katherine E. Kilpatrick; Timothy J. Lansing; Cheau Yun Chen; Marcy Engelstein; Stephen Friend; W. David Henner; T M Gilmer (1994)
GADD45 (growth arrest and DNA damage) is a DNA-damage-inducible gene regulated in part by the tumor suppressor p53. A role in negative growth control has recently been suggested based on significant (more than 75%) reduction of colony formation following over expression of Gadd45. To better understand the role of Gadd45, we have developed specific rabbit and murine antibodies raised against the human recombinant protein. Using these antibodies, we have found that in ML-1 cells Gadd45 is predominantly a nuclear protein. MyD118, a protein induced by terminal differentiation sharing 57% homology with Gadd45, does not cross-react with any of the antibodies produced. As expected, the induction of Gadd45 protein by ionizing radiation (IR) was also found to be dependent on a wild type p53 phenotype. Interestingly, WI-L2-NS, a human lymphoid cell line, showed very high basal levels of Gadd45 mRNA and protein in addition to a high constitutive level of a mutated p53 protein. In this cell line, the high levels of GADD45 did not inhibit cellular growth in spite of the fact that no mutations were found in GADD45 sequence. These results indicate that some cell line(s) can tolerate high levels of Gadd45 and abrogate its growth suppression function.